Hand, foot and mouth disease in children - Modesto dos Santos, Vitorino (2025)
Dear Editor: Hand, foot and mouth disease (HFMD) is a common childhood infection caused by coxsackieviruses (CV) A5, A6, A7, A10, A16, B1, B2, B3 and B5, and by enterovirus (EV) A71 (1-10). HFMD affects individuals of all ages, with severe cases occurring in patients aged one year or younger (1-3). A very recent review article on HFMD was published in this journal by Herrera Ortiz JU et al. which emphasizes the sanitary conditions that predispose to the increase of this disease and the need for efficient vaccination against all causative agents in order to avoid its spread and epidemic outbreaks (2). The authors analyzed 43 data sources published up to 2022, and the synthesis of this evaluation was clearly explained, which increased the general interest of healthcare workers. Given the importance of this type of research, the purpose of the following comments on new references from 2024 is to enhance the role of the aforementioned review.